Assessing the accuracy of two Bayesian forecasting programs in estimating vancomycin drug exposure. (13th August 2020) - Shingde, Rashmi V; Reuter, Stephanie E; Graham, Garry G; Carland, Jane E; Williams, Kenneth M; Day, Richard O; Stocker, Sophie L
Abstract: Background: Current guidelines for intravenous vancomycin identify drug exposure (as indicated by the AUC) as the best pharmacokinetic (PK) indicator of therapeutic outcome. Objectives: To assess the accuracy of two Bayesian forecasting programs in estimating vancomycin AUC0–∞ in adults with limited blood concentration sampling. Methods: The application of seven vancomycin population PK models in two Bayesian forecasting programs was examined in non-obese adults ( n = 22) with stable renal function. Patients were intensively sampled following a single (1000 mg or 15 mg/kg) dose. For each patient, AUC was calculated by fitting all vancomycin concentrations to a two-compartment model (defined as AUCTRUE ). AUCTRUE was then compared with the Bayesian-estimated AUC0–∞ values using a single vancomycin concentration sampled at various times post-infusion. Results: Optimal sampling times varied across different models. AUCTRUE was generally overestimated at earlier sampling times and underestimated at sampling times after 4 h post-infusion. The models by Goti et al. ( Ther Drug Monit 2018; 40: 212–21) and Thomson et al. ( J Antimicrob Chemother 2009; 63: 1050–7) had precise and unbiased sampling times (defined as mean imprecision <25% and <38 mg·h/L, with 95% CI for mean bias containing zero) between 1.5 and 6 h and between 0.75 and 2 h post-infusion, respectively. Precise but biased sampling times for Thomson et al. were between 4 and 6 h post-infusion. Conclusions: When using a single vancomycin concentration for Bayesian estimation of vancomycin drug exposure (AUC), the predictive performance was generally most accurate with sample collection between 1.5 and 6 h after infusion, though optimal sampling times varied across different population PK models.